Hukum Perjanjian dalam Ekonomi dan Bisnis di Indonesia - Meriza Elpha Darnia; M. Ikhsan; Yuda Apriansyah; Adelia Amanda Pitaloka; Nelvi Nurhaliza; Maryam Robani (Civilia: Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2023)
This article discusses the crucial role of contract law in supporting economic and business development in Indonesia. In the context of globalization and increasingly complex economic dynamics, a deep understanding of the legal framework of agreements is important for economic and business actors. This research examines various aspects of contract law, including basic principles, dispute resolution, protection of intellectual property rights, and regulations related to the diverse and dynamic business environment in Indonesia. From the analysis carried out, this research concludes that the existence of strong and reliable contract law is the main prerequisite for sustainable economic development. Guaranteeing legal certainty, protecting the rights of parties, and facilitating efficient business transactions are crucial elements in creating a conducive investment climate and encouraging inclusive economic growth.